2003
DOI: 10.1093/toxsci/kfg200
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Predicting Immunological Effects of Chemical Stressors: Characterization of a Quantitative Biomarker for Immunological Changes Caused by Atrazine and Ethanol

Abstract: Previous studies demonstrate that the effects of one chemical stressor on selected immunological parameters can be predicted on the basis of the area under the corticosterone concentration vs. time curve. However, it is not clear if this is applicable to other chemical stressors. The present study was conducted to determine if the stress-induced immunological effects of atrazine and ethanol could be predicted, and if it is feasible to use one immunological parameter as a biomarker of stress to predict the quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 32 publications
9
63
2
1
Order By: Relevance
“…High levels of ethanol consumption are known to affect the immune system (Szabo, 1999). Previous studies have reported that an oral dose of ethanol (4 to 7 g/kg) to B 6 C 3 F 1 mice slightly decreased the number of nucleated cells in the spleen but did not effect the percentage of CD4 + and CD8 + cells (Pruett et al, 2003). These results are similar to those observed in this study using ethanol vapor.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…High levels of ethanol consumption are known to affect the immune system (Szabo, 1999). Previous studies have reported that an oral dose of ethanol (4 to 7 g/kg) to B 6 C 3 F 1 mice slightly decreased the number of nucleated cells in the spleen but did not effect the percentage of CD4 + and CD8 + cells (Pruett et al, 2003). These results are similar to those observed in this study using ethanol vapor.…”
Section: Discussionsupporting
confidence: 91%
“…* Significantly different from untreated mice analyzed on the same day at p ≤ 0.05 using students 2-tailed t-test. volume of 20 mL/min, mouse body weight of 0.02 kg, ethanol vapor concentration of 60 mg/L, and 50-100% absorption of the inhaled dose, the maximum ethanol dose to mice in this study was 2.7-5.4 g/kg BW which is within the range used by Pruett et al (2003).…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies have demonstrated that atrazine at all dosages used in this study induce a significant increase in serum corticosterone (Pruett et al, 2003b).…”
Section: Dieldrin At 20 Mg/kg But Not At 10 Mg/kg Induces a Stress Resupporting
confidence: 48%
“…The concentration of corticosterone used in this experiment is approximately 10% of maximal values that might be expected to be induced by the pesticides or by poly I:C (Pruett et al, 2003b), because ∼90% of corticosterone in mouse serum is bound by corticosterone-binding globulin and not biologically available (Pruett et al, 1999). All treatments slightly but significantly decreased the survival and/or metabolic activity of the cells as indicated by the MTT assay.…”
Section: Direct Effects Of Dieldrin Atrazine and Corticosterone On mentioning
confidence: 98%
See 1 more Smart Citation